1987
DOI: 10.1177/073346488700600107
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Alzheimer-Type Dementia in Institutionalized Patients: A Cross-Sectional Study

Abstract: A gradual deterioration of mental and physical condition is one of the main clinical signs of dementia of the Alzheimer type (DA T). To describe this deterioration, we evaluated 88 institutionalized patients with DA T and plotted their current status on a number of different clinical parameters as a function of time from the estimated onset of dementia. Ratings of speech, cooperation, social contact, and communication were in the very low range in patients with duration of DA T of three years or longer, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 8 publications
0
26
0
2
Order By: Relevance
“…Patients are tested every 3 months with the Mini-Mental State examination [10], Language Assessment Scale [11], and M ACC Behavioral Adjustment Seale [ 12]. A physician or a psychologist rates the Mini-Mental State and Language Assessment Scale, while members of the nursing team rate the MACC Behavioral Adjustment Scale.…”
Section: Methodsmentioning
confidence: 99%
“…Patients are tested every 3 months with the Mini-Mental State examination [10], Language Assessment Scale [11], and M ACC Behavioral Adjustment Seale [ 12]. A physician or a psychologist rates the Mini-Mental State and Language Assessment Scale, while members of the nursing team rate the MACC Behavioral Adjustment Scale.…”
Section: Methodsmentioning
confidence: 99%
“…The inability to eat is the most life-threatening [2][3][4][5][6] of all the functional impairments in AD, with 50% of the patients losing the ability to feed themselves 8 years after diagnosis [7]. Altered eating behaviors in AD range from walking away from food at the table, to spitting out food, and choking on liquids and solids [8][9][10][11][12].…”
mentioning
confidence: 99%
“…As many as 50% of nursing home residents may require feeding assistance ranging from organizing and setting up the meal to total assistance, and 32% of nursing home residents have been reported to have swallowing problems [7]. With two exceptions [18,19], most research has focused on problems associated with institutional caregivers feeding AD residents.…”
mentioning
confidence: 99%
“…In one retro spective study based on caregivers' recall of events in past years. Volicer et al [34] reported that sleep disturbance occurred after loss of self-dressing ability but before loss of self-feeding ability and limb contractures.In this study we present data from caregiver reports of AD patients which indicated when during the 24-hour day disruption behaviors were likely to occur. By relating such reports to measures of rate of decline of mental status in AD.…”
mentioning
confidence: 99%